MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: R

There are no items in this cart.
Continue Shopping
Menu
paradox xyz cool Grade: 11
        

prove that:


tan3A.tan2A.tanA = tan3A - tan2A - tanA

6 years ago

Answers : (1)

vikas askiitian expert
510 Points
										

tan2A can be written as  tan(3A-A)


 


now we have tan(a-b)=tana-tanb/1+tanatanb


here a =2A & b=A


 


tan2A=tan(3A-A)=tan3A-tanA/1+tan3AtanA


 


tan2A(1+tan3Atan2A) = tan3A-tanA


 


 tan2A + tan2Atan3AtanA = tan3A -tanA     or


 


      tan2Atan3AtanA = tan3A -tanA-tan2A


hence proved


 

6 years ago
Think You Can Provide A Better Answer ?
Answer & Earn Cool Goodies
  • Complete JEE Main/Advanced Course and Test Series
  • OFFERED PRICE: R 15,000
  • View Details

Ask Experts

Have any Question? Ask Experts

Post Question

 
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!! Click Here for details